The Mediating Role of Psychological Inflexibility in the Relationship Between Anxiety, Depression, and Emotional Eating in Adult Individuals With Obesity - Guerrini Usubini, Anna; Varallo, Giorgia; Giusti, Emanuele Maria; Cattivelli, Roberto; Granese, Valentina; Consoli, Simone; Bastoni, Ilaria; Volpi, Clarissa; Castelnuovo, Gianluca (Frontiers in Psychology, 2022)
The aim of this cross-sectional e current study is to investigate the mediating role of psychological inflexibility in the relationship between anxiety and depression and emotional eating in a sample of 170 123 inpatient Italian adult individuals with obesity. In this cross-sectional study, participants completed the Anxiety and Depression subscales of the Psychological General Well-Being Inventory, the Acceptance and Action Questionnaire, and the Emotional Eating subscale of the Dutch Eating Behavior Questionnaire to assess anxiety and depression, psychological inflexibility, and emotional eating, respectively. Results showed that the indirect effect of PGWBI-A on DEBQ-EE through AAQ-II was significant [b=-0.0155; SE=0.076; 95% BC-CI (-0.0320 - -0.023)]. Similarly, the indirect effect of PGWBI-D on DEBQ-EE through AAQ-II was significant [b=-0.0383; SE=0.0207;95% BC-CI (-0.0810 - -0.0002)]. These findings may help to plan and develop specific psychological interventions aimed at addressing emotional eating through targeting psychological inflexibility to be included in obesity treatment programs.